Estimating estuary habitat change and functional trajectory of restoration projects over two decades in Puget Sound, WA - Chamberlin, Joshua W.; Stefankiv, Oleksandr; Beamer, Eric M.; Greene, Correigh M.; Hood, W. Gregory; Munsch, Stuart H. (Frontiers in Marine Science, 2025)
Estuaries provide many important functions for numerous aquatic species across life stages. However, these habitats have been widely impacted due to their characteristics and features that support agriculture and industrialization. Within Puget Sound, estuary restoration has been a primary tool to support recovery of Chinook salmon which are known to rely heavily on estuaries during early life history. Tracking habitat gains via restoration and evaluating effectiveness of these actions is necessary to ensure recovery targets are met. We used aerial imagery from two distinct time periods to measure estuarine habitat and estimate rates of change over two decades in Puget Sound. In addition, we developed a method to estimate functional trajectories for restoration projects based on allometry of planform geometry features for tidal deltas. A total of 72 restoration actions across nine tidal deltas added 147 ha and 410 km of tidal channel habitat in Puget Sound between 1997 and 2018. While positive overall, time series of rearing habitat change for individual tidal deltas varied reflecting the frequency and magnitude of restoration actions as well as the response of individual actions to natural processes. Estimated functional footprints for restoration projects were below total footprints for all deltas. Functional footprints appeared to track total footprint well for some deltas but indicated potential limitations in others that may be related to particular planform geometry metrics for individual sites. Overall restoration of estuarine habitats in Puget Sound since 1997 have added substantial rearing habitat in support of recovery for Chinook salmon populations. While total gains are positive, our estimates of functional trajectories provide additional information that may support adaptive management to ensure efforts remain beneficial to target species. Continuing to accurately track changes to estuarine habitat should benefit recovery efforts and support management decisions in the future.